The Neuromuscular Effects of ORG9426 in Patients Receiving Balanced Anesthesia - Francis F. Foldes; Hideo Nagashima; Hung D. Nguyen; Wilma S. Schiller; Mary M. Mason; Yoshio Ohta (1991)
In searching for a nondepolarizing muscle relaxant with intermediate duration but more rapid onset of action than the presently available compounds, the neuromuscular and circulatory effects of ORG9426 were investigated in two studies in humans receiving fentanyl, droperidol, thiopental, and nitrous oxide-oxygen anesthesia. Eighty patients, randomly assigned to one of four groups of 20 each, received 0.12, 0.16, 0.20, or 0.24 mg/kg ORG9426. In the first study, the doses (in milligrams per kilogram) of ORG9426 that caused 50% (ED50), 90% (ED90), or 95% (ED95) neuromuscular block were determined by the individual dose-response method; they were 0.170, 0.268, and 0.305 mg/kg, respectively. In the second study, after induction of anesthesia, patients received 0.6 mg/kg (about 2 x ED95) of ORG9426, either in a single bolus (group 1) or in two unequal (0.1 and 0.5 mg/kg) increments 4 min apart (group 2). After the administration of 0.6 mg/kg ORG9426, maximal neuromuscular block developed in 1.5 +/- 0.12 min in group 1 and in 1.2 +/- 0.14 min in group 2. Patients tracheas were intubated after development of the maximal neuromuscular effect of the intubating dose and after the recording of heart rate and systolic and diastolic blood pressure. There was no difference in the clinical duration of the intubating doses, which were 40.0 +/- 3.2 (15-73) min in group 1 and 39.3 +/- 2.4 (19-57) min in group 2.(ABSTRACT TRUNCATED AT 250 WORDS)